0675 The Association Between Sleep Beliefs And Sleep Behaviour In University Students. (12th April 2019) - Arora, Teresa
Abstract: Introduction: The primary objective of the study was to examine the associations between sleep beliefs and sleep outcomes in Emirati undergraduate university students. Secondary study objectives were to investigate potential relationships between sleep behaviour and physiological health outcomes including obesity and type 2 diabetes mellitus. Methods: Female university students (n=108) were recruited to a cross-sectional study from poster advertisements placed around the university. The Dysfunctional Beliefs and Attitudes about Sleep (DBAS-16) was used to assess sleep beliefs. Sleep behaviour (duration and efficiency) was objectively estimated using wrist-worn actigraphy over seven consecutive days/nights. Height (m) and body weight (kg) was objectively measured to calculate body mass index (BMI; kg/m 2 ). Internationally accepted cut points for BMI were used to determine underweight, healthy weight and overweight/obesity. Fasting blood glucose levels (mmol/L) were acquired to determine type 2 diabetes mellitus status (healthy, pre-diabetes, type 2 diabetes). Results: The majority (89.6%) of the sample held dysfunctional beliefs about sleep. The average sleep duration was 7.65 hours. Regression analysis revealed that those with dysfunctional sleep beliefs had longer average sleep duration of 43 minutes, after adjustment (β = 43.1, p<0.05). No significant associations were observed between sleep beliefs and sleep efficiency. Those who were overweight/obese had the shortest average sleep duration compared to underweight and healthy weight, although this was not statistically significant F(2, 99)=1.97, p=0.14. Those with pre-diabetes had significantly shorter average sleep duration compared to those without diabetes, t(96)=2.20, p=0.03. Conclusion: Those with dysfunctional sleep beliefs had significantly longer sleep duration compared to those holding healthy beliefs. Sleep duration was significantly shorter in those with pre-diabetes compared to healthy participants. A time-lag effect may be possible between dysfunctional sleep beliefs and sleep behaviour, therefore larger prospective studies obtaining regular follow-up data can be used to determine cause-effect relationships and sleep variability over time. Support (If Any): N/A